2014
DOI: 10.3390/su6085143
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization, Economic Development and Environmental Change

Abstract: This paper applies the pressure-state-response (PSR) model to establish environmental quality indices for 30 administrative regions in China from 2003 to 2011 and employs panel data analysis to study the relationships among the urbanization rate, economic development and environmental change. The results reveal a remarkable inverted-U-shaped relationship between the urbanization rate and changes in regional environmental quality; the "turning point" generally appears near an urbanization rate of 60%. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 17 publications
1
40
0
Order By: Relevance
“…Shen et al [16] examined the link between urbanization and resource utilization and predicted that as there was going to be an increased demand for energy and mineral resources for China's continuing urbanization plans up till 2050, the government sector needed to review and improve existing resource utilization and environmental policies to ensure sustainable urban development. Li and Ma [17] established environmental quality indices for 30 administrative regions in China from 2003 to 2011, and employed panel data analyses to explore the relationships between the urbanization rate, economic development, and environmental change, with the results revealing an inverted-U-shaped relationship between the urbanization rate and regional environmental quality changes, and a "turning point" at around a 60% urbanization rate. Zhang et al [18] studied the effects of industrial structure, infrastructure development, land use changes, and income on sustainable urban development, and found that with steady economic growth, moderate land use changes were the key to sustainable urban development.…”
Section: Introductionmentioning
confidence: 99%
“…Shen et al [16] examined the link between urbanization and resource utilization and predicted that as there was going to be an increased demand for energy and mineral resources for China's continuing urbanization plans up till 2050, the government sector needed to review and improve existing resource utilization and environmental policies to ensure sustainable urban development. Li and Ma [17] established environmental quality indices for 30 administrative regions in China from 2003 to 2011, and employed panel data analyses to explore the relationships between the urbanization rate, economic development, and environmental change, with the results revealing an inverted-U-shaped relationship between the urbanization rate and regional environmental quality changes, and a "turning point" at around a 60% urbanization rate. Zhang et al [18] studied the effects of industrial structure, infrastructure development, land use changes, and income on sustainable urban development, and found that with steady economic growth, moderate land use changes were the key to sustainable urban development.…”
Section: Introductionmentioning
confidence: 99%
“…China's water scarcity is among the great worries [4][5][6]. In China, the total water use witnessed a sharp increase from 1030 billion m 3 in 1950 to 6183 billion m 3 in 2013, while the total amount of available water resources remained relatively constant and was unevenly distributed. Thus, water shortage and related environmental issues significantly limited the sustainable development of the economy and society in China [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The scale and number of cities and towns have also grown. It has brought great challenges to resources and environment, making China one of the largest economies and consumers of resources in the world [2,3]. China's water scarcity is among the great worries [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Especially in the Western world, the nonprofit sector fulfills a broad range of socio-economic functions that are intended to strengthen the social and ecological dimensions of sustainable development (cf. [1][2][3][4]). Yet, many individual nonprofit organizations operate in a complex and turbulent environment that poses a significant challenge to their own economic sustainability (cf.…”
Section: Introductionmentioning
confidence: 99%